Measuring What Matters-A Holistic Approach to Measuring Well-Being in Endometriosis - Lori McPherson; Siladitya Bhattacharya (Frontiers Media S.A., 2021)
Endometriosis is a common condition which affects women in a number of ways and impairs their ability to live a full and meaningful life. Evaluative research has traditionally taken its cue from a medical approach which has forced women to choose one area of functioning as their primary concern, and tended to use a narrow definition of treatment success which ignores general well-being. While recent trials have included quality of life (QOL) measures as outcomes, these have not been able to capture the totality of the impact of the disease and its treatment on a woman's capability to do what she might want to do and be who she might want to be. A capability approach might overcome this barrier, but the available tools will need to be refined and validated in women with endometriosis before this can be integrated within everyday clinical and research practice.